I Am Not Your Negro Movie Review: Critical Reflection and Discourse to Advance Social Equity. (4th March 2021) - Lopez-Littleton, Vanessa; Chiarelli, Juliana; Ward, Amber; Shelby, William
Abstract : This article reviews I Am Not Your Negro, a documentary film based on Remember this House, an unfinished manuscript written by James Baldwin. I Am Not Your Negro is a critical film for any public service professional who impacts the lives and livelihoods of Black people in the United States. The critical nature of this film rests in the tragedy of lives lost in a quest for justice for Black people in the US. Baldwin's conceptualization of "the Negro problem" is an ethical concern that undergirds a strong rationale to advance social equity in American society. Using the tenets of critical race theory, we argue public service personnel have an ethical duty to actively oppose racism, reject color-blind ideology, engage in critical reflection and discourse about justice and the denial of the American dream, and pursue social equity as a means of achieving justice for all.